2017
DOI: 10.6061/clinics/2017(02)02
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the degree of correction of neuromuscular scoliosis and patient quality of life

Abstract: OBJECTIVE:There are few data on patient satisfaction with surgery for the correction of neuromuscular scoliosis or on the correlation between patient satisfaction and the degree of curve correction achieved by surgery. Our aim was to determine the correlations between both patient satisfaction and perception of quality of life and the degree of curve correction.METHODS:We interviewed 18 patients and administered a questionnaire that collected social and economic data and information about functional ability, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
2
0
3
Order By: Relevance
“…A comparable study by Nordon et al found at a mean age of 15.9 years and a mean percentage correction of 42.8% from a mean Cobb angle of 78.8 to 44.6 degrees. They also reported that patients stayed a mean average of 10 days at the hospital [28], which is slightly less than patients in Latvia with 11.8 ± 2.6 days. Although a direct comparison between these results is difficult, they may suggest that an operation at a younger age could lead to higher Cobb angle correction percentages and less hospitalization time for patients with neuromuscular scoliosis.…”
Section: Neuromuscular Scoliosismentioning
confidence: 94%
“…A comparable study by Nordon et al found at a mean age of 15.9 years and a mean percentage correction of 42.8% from a mean Cobb angle of 78.8 to 44.6 degrees. They also reported that patients stayed a mean average of 10 days at the hospital [28], which is slightly less than patients in Latvia with 11.8 ± 2.6 days. Although a direct comparison between these results is difficult, they may suggest that an operation at a younger age could lead to higher Cobb angle correction percentages and less hospitalization time for patients with neuromuscular scoliosis.…”
Section: Neuromuscular Scoliosismentioning
confidence: 94%
“…The Gross Motor Function Classification System (GMFCS) was evaluated for the NMS patients with cerebral palsy etiology at preoperatively. Bridwell’s questionnaire were used for clinical evaluation preoperatively, and/or at postoperative 2-year follow-up 11 .…”
Section: Methodsmentioning
confidence: 99%
“…Однако, несмотря на то, что исследование результатов на основе данных пациентов является важным инструментом количественной оценки воздействия лечения деформации позвоночника на состояние пациента, анализ литературы показывает, что степень доказательств улучшения функциональных результатов, качества жизни очень низка у больных с нейромышечным сколиозом [8,14]. Доказательства в поддержку улучшения качества жизни и функциональных результатов у пациентов с церебральным параличом и мышечной дистрофией Дюшенна очень слабые, a у пациентов spina bifida они отсутствуют [8].…”
Section: Ek Wai Et Al разработали действенный и надежный опросник -Spina Bifida Spineunclassified
“…Очень важно обеспечение согласованности во всех учреждениях, и это должно быть в центре будущей работы в этой области по всем результатам исследования [9]. Кроме того, в будущем было бы предпочтительно проводить каждое собеседование по телефону и/или с профессионалом, не являющимся врачом, чтобы получить более объективные ответы [14].…”
Section: заключениеunclassified
See 1 more Smart Citation